A Comparative Analysis of Radiological Imaging and Surgical Treatments for Maxillary Artery Pseudoaneurysms, Based on a Literature Review and Our Clinical Experience - Kinga Samól; Adam Michcik; Barbara Wojciechowska; Adam Polcyn; Łukasz Garbacewicz; Barbara Drogoszewska (Biomedicines)
Background/Objectives: A pseudoaneurysm forms as a result of disruption of all artery wall layers. In the head and neck, they are most commonly found in the maxillary artery. Due to their location and associated symptoms, detailed radiological imaging is necessary to determine the nature and extent of lesions. Various treatment methods are available. Methods: To systematize symptoms, diagnostics, and treatment methods, a literature review from databases spanning 2014 to 2024 was conducted, with 30 articles included in the study. Results: The factors that caused MAPs included facial trauma (n = 33; 66%), iatrogenic surgical procedures (n = 14; 28%), head and neck radiotherapy (n = 1; 2%), infection (n = 1; 2%), and one case due to an idiopathic factor (n = 1; 2%). Diagnostic imaging included computed tomography with contrast, magnetic resonance imaging, and angiography. Treatment methods used: endovascular embolization (n = 44; 88%), surgical resection (n = 3; 6%), cauterization (n = 2; 4%), and compression tamponade (n = 1; 2%). Interestingly, three of the cases were treated with endoscopic access (6%). Conclusions: It can be concluded that the most common cause of MAPs is trauma to the facial skeleton, and the most frequently used treatment method is endovascular embolization. Given the need for detailed MAP imaging and treatment in specialized invasive radiology departments, patients with MAPs should be treated in multidisciplinary clinical centers.